2023
DOI: 10.1158/1538-7445.am2023-3942
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3942: Differential expression of a novel transport receptor, SORT1 (sortilin), in cancer versus healthy tissues that can be utilized for targeted delivery of anti-cancer drugs

Abstract: Sortilin (SORT1), or neurotensin receptor-3, is a scavenging receptor in the Vacuolar Protein Sorting 10 protein (Vps10p) family. SORT1 is involved in the internalization and trafficking of its ligands through an endocytic process and is associated with cancer cell survival and progression, making SORT1 a candidate for novel drug delivery. We recently reported on the pattern and prevalence of SORT1 expression in endometrial, breast, ovarian, colorectal, pancreas cancers, and skin melanoma. To better understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…SORT1 expression is elevated in several human malignancies including breast, ovarian, prostate, colon, pancreatic, skin, and pituitary cancers ( 51 55 ). Recently, screening of 19 cancer TMAs with 2800 evaluable cancer cores confirmed that SORT1 is highly expressed in multiple tumors and may therefore be a promising target for the delivery and internalization of anticancer therapeutic agents ( 56 , 57 ). The current study employed the syngeneic SORT1-positive B16-F10 melanoma tumor model to assess the biological activity of TH1902 within the iTME and to confirm its preclinical potential for use in combination immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…SORT1 expression is elevated in several human malignancies including breast, ovarian, prostate, colon, pancreatic, skin, and pituitary cancers ( 51 55 ). Recently, screening of 19 cancer TMAs with 2800 evaluable cancer cores confirmed that SORT1 is highly expressed in multiple tumors and may therefore be a promising target for the delivery and internalization of anticancer therapeutic agents ( 56 , 57 ). The current study employed the syngeneic SORT1-positive B16-F10 melanoma tumor model to assess the biological activity of TH1902 within the iTME and to confirm its preclinical potential for use in combination immunotherapy.…”
Section: Discussionmentioning
confidence: 99%